Ovarian Hyperstimulation Syndrome - Gerris, Jan; Delvigne, Annick; Olivennes, Francois (Taylor & Francis, 2006)
Major advances have recently been made in our understanding of Ovarian Hyperstimulation Syndrome (OHSS). These include improving classification, recognizing primary and secondary risk factors, manipulating and monitoring ovarian stimulation, handling risky situations, and elucidating the underlying pathophysiologic mechanisms of the syndrome. As su